Proceedings of the 9th International Conference on Asian and Pacific Coasts 2017 (APAC 2017), SMX Convention Centre, Pasay City, Philippines, 19 - 21 October 2017 - Asian and Pacific Coasts SMX Convention Centre, Pasay City, Philippines) 19 - 21 October 2017; Suh, Kyung Duck; Cruz, Eric C.; Tajima, Yoshimitsu (New Jersey World Scientific Publishing, 2017)
This is the proceedings of the 9th International Conference on Asian and Pacific Coasts. The conference focuses on coastal engineering and related fields among Asian and Pacific countries/regions. It includes the classical topics of the coastal engineering as well as topics on coastal environment, marine ecology, coastal oceanography, and fishery science and engineering. The book will be valuable to professionals and graduate students in this field.
Electronic reproduction.
Keywords: Geography. -- Anthropology. Recreation; Physical geography; Geomorphology. -- Landforms. Terrain